Spiral Nematode, Helicotylenchus pseudorobustus (Steiner, 1941) Golden, 1956 (Nematoda: Tylenchida: Hoplolaimidae) - William T. Crow (EDIS)
Spiral nematodes of the genus Helicotylenchus are among the most ubiquitous plant-parasitic nematodes worldwide. Helicotylenchus pseudorobustus is a species common in Florida and the southeastern United States and is frequently found associated with turfgrasses and other grass hosts in the region. On most plants, it is not considered particularly damaging, but recent research has shown that this species suppresses growth of certain turfgrass hosts. Seashore paspalum, a turfgrass used in tropical and subtropical regions, is particularly susceptible to infestation. This 4-page fact sheet was written by William T. Crow and published by the UF Department of Entomology and Nematology, January 2013.